Ticlopidine and aspirin interactions. Issue 1 (January 1997) - Gregorini, L.; Marco, J.
Abstract : The risk-benefit balance when aspirin is compared with aspirin combined with ticlopidine is being investigated in several multicentre trials (MUSIC and WEST II versus TASTE, MUST, and STARS respectively). Cardiologists follow one of two strategies. Some prefer a more aggressive antiplatelet regimen, disregarding the risk of neutropenia (0.7%) because they want to avoid lessening the therapeutic effect of vessel patency obtained with stent implantation. Others give only aspirin (a money saving approach) confident that IVUS inspection (an expensive approach) will allow an adequate evaluation of full stent expansion and lesion coverage, despite a more pronounced activation of the coagulation cascade. Our impression so far is that the combination of ticlopidine and aspirin has a more favourable risk-effect balance.